The Analysis of Internet Usage on the Biological Evolution of Human Behavior - Hasibuan, Hotmaidah (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The Internet as a revolutionary innovation in communication, has rapidly evolved since it's inception and plays a central role in human life. This research uses a qualitative method with a multidisciplinary approach, involving the analysis of scientific literature and case studies. The evolution of this technology reflects biological principles found in nature, such as selection, adaptation, and diversification. In the context of human evolution, the internet has become an important extension of cognitive and social abilities, enabling the rapid dissemination of information and creating interaction spaces that transcend geographical boundaries. Biological evolution enables the emergence of intelligence in living beings. On the internet, advancements in technology such as artificial intelligence (AI) are the result of a